Rancang Bangun Sistem Pelatihan Menembak dengan Sinar Laser Dimonitor Menggunakan Smartphone - Widyo Sasmito (Politeknik Negeri Malang, 2018)
Shooting drills were carried out with very limited ammunition support. This is easy to understand because shooting drills are expensive and have a very high safety risk. Therefore, in order for shooting practice to be optimal, safe, inexpensive and can be carried out at any time, it is necessary to immediately realize shooting practice by utilizing advances in science and technology (lasers). The aim of this research is to develop a shooting training system with laser firing to save bullets during shooting practice and to make it easier for shooters and judges to monitor the results of shooting accuracy via the web or smartphone. The system itself consists of a laser and light sensor which is interfacured with a microcontroller and wifi shield as data transmission.